Advanced materials : proceedings of the International Conference on "Physics and Mechanics of New Materials and Their Applications", PHENMA 2019 /: proceedings of the International Conference on "Physics and Mechanics of New Materials and Their Applications", PHENMA 2019. ([2020]) - Unknown
No abstract available